The role of inter-kingdom interactions in chlorine resistance of biofilms formed by drinking water-isolated microorganisms - Simões, Lúcia C. (2016)
Biofilms in drinking water distribution systems (DWDS) are responsible for several undesirable effects in water. One of the main drawbacks is their potential to protect pathogens from stress conditions. Microbial interactions in biofilms can benefit the survival of co-existing microorganisms, including the increased resistance to antimicrobials. Chlorination is the main widespread strategy used in DWDS for microbial control. Even if new and alternative strategies are being developed, it is conceivable that the future strategies still persist with chlorine due to economic and safety aspects. Therefore, the understanding on the efficacy of chlorine against biofilms is of utmost importance in order to improve the current strategies. The purpose of this work was to assess the effects of sodium hypochlorite (SHC) on the control of single and dual-species biofilm formation by selected filamentous fungi (Penicillium expansum and Penicillium brevicompactum) and bacterium (Acinetobacter calcoaceticus) isolated from DWDS. Biofilms were developed during 48 h in 96-wells microtiter plates under two hydrodynamic conditions (25 and 150 rpm). The effects of SHC at several concentrations (0.1, 0.5, 1, 10 and 100 mg/L) was tested. The results shown that, P.brevicompactum biofilms were extremely resistant to disinfection when compared with single-species biofilms of P.expansum and dual-species biofilms of P.brevicompactum-A.calcoaceticus. The association of A.calcoaceticus with both fungi seems beneficial, since the dual-species biofilms were more resistant to disinfection. The inactivation and removal occurred for high SHC concentrations. However, total biofilm control was not achieved.